Penguatan Pembelajaran Bermakna melalui Pelatihan Model Deep Learning Berbasis Media Canva di SMPN 2 Mappakasunggu (International Forum of Researchers and Lecturers, 2026)
Meaningful learning is a crucial requirement in 21st-century education, particularly in the face of the increasingly rapid development of digital technology. However, teachers' limited knowledge and skills in utilizing digital learning media remain a challenge, particularly in junior high schools. This study aims to analyze the strengthening of meaningful learning through training on the Canva-based deep learning model at SMP Negeri 2 Mappakasunggu. This study used a quantitative approach with a one-group pretest–posttest pre-experimental design. The subjects were teachers at SMP Negeri 2 Mappakasunggu who participated in the training as part of the Community Service Program (KKN). The research instrument was a knowledge test on Canva administered before (pretest) and after (posttest) training. Data were analyzed using descriptive statistics and N-Gain calculations. The results showed that the average pretest score for teachers was 42.3 with a range of 30–55, while the average posttest score increased to 70.8 with a range of 65–76. The N-Gain calculation of 0.49 is in the moderate category. These findings indicate that training on the Canva-based deep learning model is effective in enhancing teacher knowledge and supporting meaningful learning. This study recommends the continued implementation of similar training to improve the quality of technology-based learning in schools.